THE (IN) SECURITY OF INFORMING AUDIENCE IN NOWADAY'S MEDIA CASE STUDY: CLONING ROMANIAN NEWS WEBSITES - Ungur-Brehoi , Carmen (International Journal of Legal and Social Order, 2024)
Informing the public correctly these days is not as simple as we might think, in the "communication age", despite the diversity of tools and the fast pace at which news can be disseminated in real time. Journalists and online channels face significant challenges, dealing not only with disinformation, propaganda or fake news, but also with other larger impediments such as cyber-attacks, phishing, website cloning, scams and distribution of malware. Cloning incidents involving the Romanian media have been sporadically reported over the years, especially during significant events, political elections or crises. of all kinds This article aims to highlight some of these cases in recent years that contribute to a state of insecurity among online readers.